Prefix “Neo” in the Cultural and Scientific Reflection - Veronika B. Zuseva-Özkan (Studia Litterarum)
The article considers the main vectors of the cultural and scientific reflection of the prefix “neo”. The author describes the notions of the cultural retrospection and of the retrospective movements in world literature, reveals their invariant features (recurrent character, high variability, controversiality, syntheticism, tendency to produce the third-order movements, self-reflexivity). The state of culture abundantly producing the retrospective movements is discussed in relation to the ideas of the “end of history” (F. Fukuyama), the “random cannibalization” of historical styles (F. Jameson), the “invalidation” of language (H. Lefebvre), the cultural recontextualization (L. Hutcheon), the “culturology of prefixes” (S. Zenkin). The author proposes ways of perceiving the “retrospective dimension” of the cultural theory based on various concepts of the literary process: filiational, i. e. focusing on interaction between tradition and the individual talent; systematic dynamic concept involving not the separate texts or authors but the whole artistic systems; receptive aesthetics; historical poetics.